Fixed field alternating gradient accelerator with small orbit shift and tune excursion - Sheehy, S; Peach, K; Witte, H; Kelliher, D; Machida, S (2010)
A new design principle of a nonscaling fixed field alternating gradient accelerator is proposed. It is based on optics that produce approximate scaling properties. A large field index k is chosen to squeeze the orbit shift as much as possible by setting the betatron oscillation frequency in the second stability region of Hill's equation. Then, the lattice magnets and their alignment are simplified. To simplify the magnets, we expand the field profile of rk into multipoles and keep only a few lower order terms. A rectangular-shaped magnet is assumed with lines of constant field parallel to the magnet axis. The lattice employs a triplet of rectangular magnets for focusing, which are parallel to one another to simplify alignment. These simplifications along with fringe fields introduce finite chromaticity and the fixed field alternating gradient accelerator is no longer a scaling one. However, the tune excursion of the whole ring can be within half an integer and we avoid the crossing of strong resonances. © 2010 The American Physical Society.